COMMUNICATION PATTERN INSTRUCTOR USE OF CYBER EXTENSION AT SECRETARIAT AGENCY COORDINATION COUNSELING PROVINCE RIAU - Zulafni Adriana; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The existence of the internet has influenced major changes in the patterns of communication. Presence Cyber Extension aims to develop a web-based agricultural information system remains effective, timely , targeted and changing communication patterns bring a change of direction of becoming a two-way communication .The purpose of this study to determine how the message flow in the use Cyber Extension , to determine the form of communication to use Cyber Extension and determine the factors supporting and inhibiting communication pattern educator to use Cyber Extension .This research used qualitative method with descriptive approach. The data collected by doing observation, interview, and documentation. There are 10 participants taken by purposive technique for this research. This research used the interactive data analysis from Miles and Hubermen by using examination of validity technique thorough the extension of membership and triangulation.The results of research show communication pattern instructor use of Cyber Extension is the message flow two way, where the two-way communication can also be done with upward communication , downward communication and communication diagonal . This form of communication to use Cyber Extension extension is done by direct communication is discussed and plunge into a field instructor and indirect communication is by using the internet Cyber Extension . Factors supporting the extension of the use of communications Cyber Extension is the availability of information on Cyber Extension and inhibiting tissue factor and lack of willingness to take advantage of Cyber Extension educator.Keyword : Communication Pattern , Communication Instructor, Cyber Extension.